Hubungan Peningkatan Physical Literacy Melalui Penjas terhadap Aktivitas Fisik Siswa Remaja - Andika; Saputra, Endarman; Oktadinata, Alek (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Physical literacy represents an individual's capacity to utilize movement abilities, knowledge, and motivation to engage continuously in physical activities throughout their lifetime. This concept underlines that physical literacy serves as a fundamental foundation for creating healthy, dynamic, and meaningful lifestyle patterns. Physical activities constitute one of the primary determinants influencing nutritional conditions among adolescent groups; however, basic health research findings indicate that 67.2% of individuals aged over 10 years demonstrate inadequate levels of physical activity. This study aims to evaluate the correlation between physical literacy enhancement through physical education subjects and the level of physical activity among adolescent students at SMP Negeri 5 Jambi City. The research methodology employs a quantitative approach with correlational design involving 48 grade VIII students. Research findings indicate that physical literacy provides positive and significant influence on adolescent physical activity, demonstrated by t-calculated values greater than t-table and significance levels less than 0.05.